Live from Dar es Salaam : Popular Music and Tanzania's Music Economy - Perullo, Alex (Book collections on Project MUSE., 2011)
When socialism collapsed in Tanzania, the government-controlled music industry gave way to a vibrant independent music scene. Alex Perullo explores the world of the bands, music distributors, managers, and clubs that attest to the lively and creative music industry in Dar es Salaam. Perullo examines the formation of the city's music economy, considering the means of musical production, distribution, protection, broadcasting, and performance. He exposes both legal and illegal strategies for creating business opportunities employed by entrepreneurs who battle government restrictions and give flight to their musical aspirations. This is a singular look at the complex music landscape in one of Africa's most dynamic cities.